Peningkatan Hasil Belajar Siswa dengan Menggunakan Alat Peraga pada Materi Balok di Kelas V SD Kemala Bhayangkari Banda Aceh - Fatimah Fatimah (Jurnal Dedikasi Pendidikan, 2018)
Updating teaching, applying appropriate methods, provision of instructional media should primarily be done in Mathematics education, because in Mathematics education in general, there are still many obstacles and problems encountered, such as the value of children for subjects of low Mathematics, Mathematics lessons have no meaning as part in life eans –day, Math lesson is still regarded as a difficult lesson, learning mathematics conducted by teachers still tend to be conventional, lack of application of demonstration methods in learning Mathematics, lack of innovative power, creativity in learning Mathematics make this subject is not liked by children. The purpose of this study is to determine the improvement of student learning outcomes by using media on the material beams in class V SD Kemala Bhayangkari. This research was conducted in class V SD Kemala Bhayangkari, the subject of this research is the students of grade V SD Kemala Bhayangkari with the number of 20 students. This type of research is a classroom action research consisting of two cycles. The results obtained as many as 19 students or 95% complete and 1 student or 5% students are not complete. It means that there is an increasing of the students' learning mastery. This increase is as expected above 75% of the total number of students. This 95% completeness criterion above 75% indicates that the improvement of learning in cycle II has been successful.Keywords : Media, Material Beam